Pendidikan Arsitektur dan Edukasi tentang Bambu sebagai Material Ramah Lingkungan - Luluk Maslucha; Yulia Eka Putrie; Aisyah Nur Handryant; Sukmayati Rahmah (Program Pascasarjana Universitas Brawijaya, 2020)
The urgency of education about bamboo in architectural education is closely related to various problems and contemporary phenomena in the field of settlement and the environment. As an environmentally friendly alternative material, bamboo has various potentials that are generally still underestimated by common people and society. Architecture education students and graduates have an important role in the exploration of this potential, as well as its dissemination to the public at large. However, positive changes and solutions to the problems above will not be achieved without serious efforts in architectural education to instill knowledge, abilities, and awareness about the potential of bamboo to their students. This research is an evaluation of bamboo education to architecture undergraduate students, especially in the Department of Architecture, UIN Maulana Malik Ibrahim Malang. An evaluation of the level of knowledge, abilities, and sensitivity of students regarding various bamboo potentials is carried out with the aim of formulating various strategies and learning methods that are more appropriate.